Forensic validation studies of a novel 35-InDel multiplex polymerase chain reaction system - Tong Xie; Hui Xu; Congying Zhao; Yating Fang; Yongsong Zhou; Qiong Lan; Chunmei Shen; Bofeng Zhu (Wolters Kluwer Medknow Publications, 2023)
Background: A difficulty associated with forensic applications is the detection of degraded biological materials. Due to the large amplicon sizes of short tandem repeat alleles, valid genotyping results cannot be obtained from degraded biological materials. Recently, insertion/deletion (InDel) polymorphisms have been used in forensic applications for their widespread distributions in the human genome, short amplicon sizes, and low mutation rates. Purpose: Human identification InDel panels have mostly been designed for European populations. Therefore, our laboratory independently developed a multiplex polymerase chain reaction (PCR) system with 35 polymorphic InDel loci to be used for human identification in China. Forensic validation studies were conducted on this novel 35-InDel multiplex PCR system. Methods: The 35 InDel loci were screened in the database, and then used with the traditional PCR amplification and capillary electrophoresis platform combined with five-color fluorescence parallel detection technology. Validation studies were performed on this novel panel, including accuracy, repeatability and reproducibility, species specificity, sensitivity, stability, forensic case sample detection, and mixture studies. In addition, forensic efficiency assessments were conducted in populations from different continents. Results: The data of validated studies indicated that the novel 35-InDel panel was accurate, stable, and efficient for forensic purposes. For human identification, the cumulative power of discrimination values for the these 35 InDel loci in East Asian, South Asian, European, American, and African populations were 0.999999999999995, 0.999999999999995, 0.999999999999971, 0.9999999999999960, and 0.999999999998166, respectively. Conclusions: In this study, a set of 35 InDel loci were conducted in a multiplex amplification system for human identification of degraded DNA sample, and this new assay was efficient and stable. The present results suggested that the 35-InDel panel was a reliable tool for forensic use and could be efficiently used for human identification in the East Asian populations.